2007
DOI: 10.1124/dmd.106.013581
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Characterization of Genetic Variants of Human Organic Cation Transporters in a Korean Population

Abstract: ABSTRACT:Genetic variants of three human organic cation transporter genes (hOCTs) were extensively explored in a Korean population. The functional changes of hOCT2 variants were evaluated in vitro, and those genetic polymorphisms of hOCTs were compared among different ethnic populations. From direct DNA sequencing, 7 of 13 coding variants were nonsynonymous single-nucleotide polymorphisms (SNPs), including four variants from hOCT1 (F160L, P283L, P341L, and M408V) and three from hOCT2 (T199I, T201M, and A270S),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
67
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 29 publications
8
67
0
Order By: Relevance
“…5A) was found, which was in line with data from a Korean population. 53 Remarkably, the haploblock structure of our 150 liver bank samples (Fig. 5A) is comparable to the HapMap data of northern/western Europeans (Supporting Fig.…”
Section: Discussionsupporting
confidence: 81%
“…5A) was found, which was in line with data from a Korean population. 53 Remarkably, the haploblock structure of our 150 liver bank samples (Fig. 5A) is comparable to the HapMap data of northern/western Europeans (Supporting Fig.…”
Section: Discussionsupporting
confidence: 81%
“…This analysis showed that there were three genotypes (GG, GT, and TT) at position 808 in the SLC22A2 gene in Chinese Hans with T2DM. The genotype in the two groups and the total group were in accordance with Hardy-Weinberg equilibrium, and the T allele frequency was 12.9%, which was similar to the data in healthy populations from Hong Kong (13.3%), Japan (16.8%), and Korea (11%) [13,20,21] . This research further investigated the relationship between the SLC22A2 808G>T polymorphism and plasma lactate levels in these T2DM patients treated with or without metformin.…”
Section: Discussionsupporting
confidence: 69%
“…77 Consistent with most of the clinical data except the study of Chen et al 73 , the in vitro functional literature suggests that the effect of the rs316019 minor allele is associated with significant reductions in the transport of model OCT2 substrates. 78,79 Thus ~19%-28% of European, East Asian, and Yoruban ancestry populations may be carriers of a reduced function OCT2 protein. Further in vivo and in vitro research on OCT2 variation and effects on drug disposition is needed.…”
Section: Discussionmentioning
confidence: 99%